KEBIJAKAN KEBIJAKAN DALAM ORGANISASI BIROKRASI MODERN - Biga, Mahyudin (Jurnal Legalitas, 2009)
The Policy is core decisions or action choices that is directly arranges management and distribution of natural resources, financial and man for the benefit of public, namely publics, resident, public or citizen. Policy is result from existence of synergy, compromise or even competition between various ideas, theory, ideology and importances representing political system a state. Because every policy made by government sealalu is concerning public importance, hence the policy called as public policy In the eyes of ideal of bureaucracy undertakes connects importance of state and public with one commitment of service that is increasing from time to time. Thereby a bureaucrat must enjoy the work without making it burden that is impressing weighs, when having to serves public with various the requirement. Bureaucracy is government infrastructure that is widely has duty and the role of as public service. the Duty and role sticks in each bureaucrat, either civil and also military receiving salary from government Hence, aparatur bureaucracy must reflect importances of public to be adopted and orthogonal transformation as position choice in executing the duty and role